Seasonal patterns of Scotogramma trifolii Rottemberg (Lepidoptera: Noctuidae) migration across the Bohai Strait in northern China. (April 2018) - He, Limei; Fu, Xiaowei; Huang, Yunxin; Shen, Xiujing; Sun, Xiaoting; Wu, Kongming
Abstract: The clover cutworm, Scotogramma trifolii Rottemberg (Lepidoptera: Noctuidae), is a serious polyphagous insect pest of Triticum aestivum Linnaeus, Zea mays Linnaeus, Gossypium herbaceum Linnaeus, and cruciferous vegetables in Asia and Europe. Although S. trifolii has been documented as a long-distance migratory species, the seasonal pattern of migration and the mating status associated with migration in this species have not been fully understood. In this paper, a set of multi-year monitoring data concerning S. trifolii migration was reported. The monitoring study was conducted by searchlight trapping on a small isolated island at the center of the Bohai Strait in northern China in 2003–2015. Data analyses showed that there were significant seasonal differences in the migration of S. trifolii moths across the sea, in which the expected numbers of moths caught per day in July through September were much higher than in the rest of months. The percentage of trapped moths was significantly female biased. The vast majority of females trapped in August and September were virgins, with little or no ovarian development. In contrast, most females trapped in May to July had mated and been sexually mature. The results suggest that S. trifolii migrates toward the north in prevailing southerly winds during late-spring (May) and early-summer (June and July), and returns to the south in prevailing northerly winds during late-summer and early-autumn. These findings may help improve the regional forecast and management of S. trifolii . Highlights: There were significantly seasonal differences in the number of S. trifolii migrant moths trapped per night. The percentage of trapped moths was significantly female biased. The vast majority of females trapped in August and September were virgins, with little or no ovarian development. Most females trapped in May to July had mated and shown some degree of ovarian development. S. trifolii likely migrated toward the north with prevailing southerly winds in early season, and returned to the south with prevailing northerly winds in late season.